Pollen phenols of the genus Zea - Almaraz-Abarca, Norma; Rivera-Rodríguez, Diana María; Arráez-Román, David; Segura-Carretero, Antonio; Sánchez-González, José de Jesús; Delgado-Alvarado, Amanda; Ávila-Reyes, José Antonio (Instituto de Ecología, A.C., 2013)
The variability of the pollen phenol composition of 32 populations of Zea mays subsp. mexicana, Zea mays subsp. parviglumis, Zea mays subsp. mays, Zea diploperennis, Zea perennis, and Zea luxurians from Mexico and Guatemala were analyzed. The phenol profiles were assessed by HPLC-DAD, and UPLC-TOF-MS. A total of 23 phenolics (four phenolic acids, 16 flavonols, and three dihydroflavonoids) were found. Quercetin glycosides (seven derivatives besides the quercetin aglycone itself) were the predominant compounds in the pollen of all analyzed species and subspecies. The major compound in all the samples, including the pollen of maize, was identified as quercetin-3,3’-O-diglucoside. The pollen of all the species and subspecies of Zea examined showed very similar patterns of accumulated phenols; however, variation in the minor compounds (phenolic acids and dihydroflavonoids) allowed to discern some inter- and intraspecific variations, although the split of Zea in the sectionsLuxuriantes and Zea was not clearly supported. The low level of variability of the pollen phenol profiles throughout the genus Zea supports the proposal that maize and some teosintes are conspecific groups, and indicates that the pollen phenol composition is highly conserved in the different taxa of Zea.